5 Differentiating transient epileptic amnesia from epilepsy in dementia and mild cognitive impairment. Issue 8 (20th July 2020) - Baker, John; Savage, Sharon; Zeman, Adam
Abstract : Objectives/Aims: Patients with TEA experience epileptic seizures characterised primarily by a transient impairment of memory. These seizures sometimes include brief periods of unresponsiveness and other ictal features, including olfactory hallucinations and motor automatisms. TEA patients also report interictal memory difficulties: autobiographical amnesia, accelerated long-term forgetting, and topographical amnesia. Epileptic seizures in dementia can lead to behavioural arrest and altered responsiveness, as well as periods of increased confusion and amnesia. We aimed to compare and contrast these conditions with the objective of developing a decision aid to distinguish them efficiently in typical clinical settings. Methods: This retrospective study examined the case notes of two groups of patients enrolled in two separate studies. The Impairment of Memory in Epilepsy (TIME) study has established a cohort of 115 patients with TEA. The Presentation of Epileptic Seizures in Dementia (PrESIDe) study assessed 144 patients with MCI or dementia and identified a clinical suspicion of epilepsy in 37 (25.7%). The Addenbrooke's Cognitive Examination - Version III (ACE-III) scores were compared as a measure of cognitive function. The prevalence of several key seizures features in both the TEA and epilepsy in dementia populations were identified. Results: The average age of seizure onset in the dementia group was 76.91 years, 15 years older than in the TEA group. A range of seizure features were seen in both groups. PrESIDe patients were more likely to have seizures where loss of awareness was a feature. Automatisms occurred in a similar prevalence across both groups, although olfactory hallucinations were significantly more common in the TEA group, as were seizures where amnesia was the sole manifestation. More than 50% of participants in both groups experienced amnestic episodes on waking. Patients with epilepsy in dementia scored significantly lower than patients with TEA on all domains of the ACE-III. However, despite typically normal results on the ACE-III, patients with TEA demonstrate impairments when recall is tested over longer delays (>24 hrs), or on measures of autobiographical memory. Conclusions: In patients with TEA, the onset of seizures occurs at a younger age than in patients who experience seizures as a feature of their dementia, there are also key differences in the types of seizure reported by these two groups of patients. In contrast to patients with dementia, those with TEA commonly perform normally on standard cognitive tests.